Adrenal venous sampling in primary aldosteronism: lessons from over 600 single-operator procedures. Issue 2 (February 2022) - So, C.B.; Leung, A.A.; Chin, A.; Kline, G.A.
Abstract : Adrenal vein sampling (AVS) is a recommended if not required final diagnostic step in the investigation of primary aldosteronism, the most common cause of remediable secondary hypertension. Successful adrenal vein sampling is operator-dependent. Having performed over 600 such procedures at our centre over 20 years, our single-operator experience is described in detail for the purpose of training future radiologists as well as for use by those who are planning to start an AVS programme of their own. This updated review considers new developments in primary aldosteronism disease understanding that are relevant for AVS performance and protocols, along with technical enhancements that may be used for special cases. Detailed understanding of variant anatomy and tips for successful cannulation are keys to success, along with an endocrinology and clinical chemistry partnership for continuous quality control. A successful AVS programme offers patients a hope for cure of resistant hypertension.